Micropaleontology or paleomicrontology? Adjusting the morphology of the word - Petró, Sandro Monticelli (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2017)
Language is dynamic, and new words should be created, through morphological correctness, when a more accurate and better way is found to communicate meaning. The word micropaleontology was coined wrongly, because it apparently portrays a microscopic scientific area, not a science whose object of study is microscopic. Unlike the microfossil, that is a microscopic fossil, a micropaleontologist is not a microscopic human being studying fossils. So, the word micropaleontology and others derived from it do not have a satisfactory morphology. The objective of this work is to propose a term that better characterizes the study of microfossils. Comparing the case of the word microphotography, which has been corrected for photomicrography, it is possible to conclude that the prefix 'micro' could be put in the middle of the word, as an infix. Thus, it would be also possible to transfer the prefix 'micro' to the middle of the word micropaleontology. So, herein the word paleomicrontology is proposed: palaiós (old) + mikrós (little) + óntos (being) + lógos (study). Therefore, even if the word micropaleontology is still considered correct, the word paleomicrontology should be also accepted in scientific studies.
Keywords: Paleontology; Portuguese Language; Neologism